Differentiation and Mineralization of Murine Mesenchymal C3H10T1/2 Cells in Micromass Culture - Roy, Rani (2010)
The murine mesenchymal cell line, C3H10T1/2 in micromass culture undergoes chondrogenic differentiation with the addition of BMP-2. This study compares the use of BMP-2 vs. insulin, transferrin, and sodium selenite (ITS) to create a chondrogenic micromass cell culture system that models cartilage calcification in the presence of 4mM inorganic phosphate. BMP-2 treated cultures showed more intense alcian blue staining for proteoglycans than ITS treated cultures at early time points. Both ITS and BMP-2 treated cultures showed similar mineral deposition in cultures treated with 4mM phosphate via von Kossa staining, however FTIR spectroscopy of cultures showed different matrix properties. ITS treated cultures produced matrix that more closely resembled mouse calcified cartilage by FTIR analysis. (45)Ca uptake curves showed delayed onset of mineralization in cultures treated with BMP-2, however they had an increased rate of mineralization (initial slope of (45)Ca uptake curve) when compared to the cultures treated with ITS. Immunohistochemistry showed the presence of both collagens type I and type II in BMP-2 and ITS treated control (1mM inorganic phosphate) and mineralizing cultures. BMP-2 treated mineralizing cultures displayed more intense staining for collagen type II than all other cultures. Collagen type X staining was detected at Day 9 only in mineralizing cultures treated with ITS. Western blotting of Day 9 cultures confirmed the presence of collagen type X in the mineralizing ITS cultures, and also showed very small amounts of collagen type X in BMP-2 treated cultures and control ITS cultures. By Day 16 all cultures stained positive for collagen type X. These data suggest that BMP-2 induces a more chondrogenic phenotype, while ITS treatment favors maturation and hypertrophy of the chondrocytes in the murine micromass cultures.